2018
DOI: 10.1007/s00784-018-2396-z
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in Alzheimer’s disease: a multicenter case-control study

Abstract: Clinicians should be aware of the implications of Alzheimer's disease in oral health, in order to stablish the effective preventive measures and the optimal treatment plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 30 publications
4
78
1
2
Order By: Relevance
“…Oral lesions, like candidiasis, angular cheilitis, and others, such as ulcerations and stomatitis, have also been reported as being more frequently observed in older adults with dementia when compared to older adults without dementia. The same trend applies to xerostomia …”
Section: Oral Health Status Among Patients With Alzheimer's Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Oral lesions, like candidiasis, angular cheilitis, and others, such as ulcerations and stomatitis, have also been reported as being more frequently observed in older adults with dementia when compared to older adults without dementia. The same trend applies to xerostomia …”
Section: Oral Health Status Among Patients With Alzheimer's Diseasementioning
confidence: 99%
“…These conditions are common among older adults in general and, consequently among older adults with Alzheimer's disease, who present with these oral health conditions even before the onset of Alzheimer's disease. Poor oral hygiene, mainly due to the above mentioned general health and social support factors, is also a common oral health‐related ROHD risk factor among older adults with Alzheimer's disease …”
Section: Oral Health Status Among Patients With Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…One study showed that patients with AD had bad oral health in comparison to a healthy age‐matched group. Patients with AD had more caries, periodontal disease, candidiasis, and salivary quantity and quality changes . In our study, we did not evaluate mucosal lesions, and all patients were edentulous.…”
Section: Discussionmentioning
confidence: 79%